2010
DOI: 10.1186/1476-4598-9-137
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-tumor activity of a new curcumin-related compound against melanoma and neuroblastoma cells

Abstract: BackgroundSharing the common neuroectodermal origin, melanoma and neuroblastoma are tumors widely diffused among adult and children, respectively. Clinical prognosis of aggressive neuroectodermal cancers remains dismal, therefore the search for novel therapies against such tumors is warranted. Curcumin is a phytochemical compound widely studied for its antioxidant, anti-inflammatory and anti-cancer properties. Recently, we have synthesized and tested in vitro various curcumin-related compounds in order to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 34 publications
9
57
0
Order By: Relevance
“…The D6 compound was proved to promote apoptosis in melanoma cells through the mitochondrial intrinsic pathway [21]. In vivo assays on mouse models confirmed the potential of D6 against melanoma, showing a significant reduction of the tumour mass growth as compared to untreated control [21]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D6 compound was proved to promote apoptosis in melanoma cells through the mitochondrial intrinsic pathway [21]. In vivo assays on mouse models confirmed the potential of D6 against melanoma, showing a significant reduction of the tumour mass growth as compared to untreated control [21]. …”
Section: Introductionmentioning
confidence: 99%
“…This genomic technology is useful to dissect the molecular changes occurring inside cancer cells, and it is well documented for malignant melanoma [22,23]. In our study, the LB24Dagi (LB24) primary melanoma cell line was selected for all the analyses, because it had been previously demonstrated to be the most sensitive line to D6 treatment among tested ones [21]. Several molecular changes that can justify the antiproliferative and proapoptotic properties of D6 on melanoma cells and likely contribute to its anti-tumour effect have been here presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…This has led the way for researchers to further study the structure-activity relationship of curcumin in medicinal chemistry [209, 210]. Interestingly, Pisano et al [211] recently showed that a new curcumin analog alpha,beta-unsaturated ketone D6 [(3E,3'E)-4,4'-(5,5',6,6'-tetramethoxy-[1,1'-biphenyl]-3,3'-diyl)bis(but-3-en-2-one)] (Fig. 5E) was more effective at inhibiting melanoma cell growth and inducing apoptosis in vitro and in vivo when compared to curcumin [211, 212].…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…Interestingly, Pisano et al [211] recently showed that a new curcumin analog alpha,beta-unsaturated ketone D6 [(3E,3'E)-4,4'-(5,5',6,6'-tetramethoxy-[1,1'-biphenyl]-3,3'-diyl)bis(but-3-en-2-one)] (Fig. 5E) was more effective at inhibiting melanoma cell growth and inducing apoptosis in vitro and in vivo when compared to curcumin [211, 212]. Other curcumin analogs (FLLL32 and FLLL62) (Fig.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…Recent advances in view of selecting new antitumor agents with more potent and selective growth inhibitory activity has revolutionized the synthesis and testing of several analogous "curcumin-like" compounds. For instance the compound , -unsaturated ketone D6 was shown to be more effective in inhibiting melanoma growth when compared to curcumin [44]. Synthetic curcuminoid derivatives have been analyzed in vivo to test their inhibitory role to tumor-specific angiogenesis such that in mice injected with melanoma cells an intraperitoneal administration of tetrahydro curcumin, salicyl curcumin and curcumin III reduced the number of induced tumor-directed capillaries.…”
Section: Curcuminmentioning
confidence: 99%